Typification of the name Cirsium lacaitae (Asteraceae) - Del Guacchio, Emanuele; Caputo, Paolo; Iamonico, Duilio (Phytotaxa, 2019)
As part of ongoing studies on the taxonomy of Cirsium Miller (1754: no pagination) sect. Eriolepis (Cassini in Cuvier 1826: 331) Dumortier (1827: 74) (Asteraceae) (Del Guacchio & Iamonico 2015), and in the context of the “Italian loci classici census” project (see e.g., Domina et al. 2012, Peruzzi et al. 2019), aimed at typifying all the names of taxa described from Italy and at improving their systematic knowledge (Vallariello et al. 2016, Del Guacchio et al. 2017, Iamonico et al. 2017, Santangelo et al. 2017), we here present a note concerning the name C. lacaitae Petrak (1914: 456), which appears still not typified.